A different perspective on sofosbuvir‐ledipasvir treatment of patients with HCV genotype 1b cirrhosis: The ital‐c network study. Issue 1 (30th August 2017) - Barone, M.; Iannone, A.; Shahini, E.; Ippolito, A. M.; Brancaccio, G.; Morisco, F.; Milella, M.; Messina, V.; Smedile, A.; Conti, F.; Gatti, P.; Santantonio, T.; et al.
Summary: The effectiveness of a 12‐week course of sofosbuvir‐ledipasvir in treatment‐experienced HCV genotype 1b‐infected patients with cirrhosis is still under debate. Our primary endpoint was to compare the sustained virological response at post‐treatment week 12 (SVR12) of sofosbuvir‐ledipasvir in combination with ribavirin for 12 weeks, and sofosbuvir‐ledipasvir alone for 24 weeks. This was a prospective observational study that enrolled 424 (195 naive, 229 experienced; 164 treated for 12 weeks with Ribavirin and 260 with sofosbuvir‐ledipasvir alone for 24 weeks) consecutive HCV genotype 1b‐infected patients with cirrhosis. The SVR12 rates were 93.9% and 99.2% in patients treated for 12 and 24 weeks, respectively ( P = .002). The baseline characteristics of patients treated for 12 weeks were significantly different from those treated for 24 weeks as regards their younger age ( P = .002), prevalence of Child‐Pugh class A ( P = .002), lower MELD scores ( P = .001) and smaller number of nonresponders ( P = .04). The shorter treatment was significantly associated with a lower SVR12 in univariate and multivariate analyses ( P = .007 and P = .008, respectively). The SVR rate was unaffected by age, gender, BMI, Child‐Pugh class, MELD score or previous antiviral treatment. Patients receiving ribavirin experienced more episodes of ascites and headache but less recurrence of hepatocellular carcinoma (HCC), and were prescribed more diuretics and cardiopulmonary drugs. No patient discontinued treatment. The therapeutic regimen of sofosbuvir‐ledipasvir plus ribavirin administered for 12 weeks was less effective than sofosbuvir‐ledipasvir alone given for 24 weeks. At odds with European guidelines, the recommended 12‐week treatment with sofosbuvir‐ledipasvir alone might be suboptimal for this setting of patients.